Soziale Infrastruktur im Kontext städtischer Schrumpfung: Räumliche Ordnungskonzepte 2015 für Kindergärten und Altenpflegeheime in Bremerhaven - Koch, Katharina (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
This article develops a number of spatial-order concepts designed to steer the implementation of the quantitative adjustments that need to be made to the provision of social infrastructure close to where the users of these facilities live. Against the background of the aim to provide parity of provision throughout the entire territory, the aim of these concepts is show how such facilities might best be distributed in terms of location in the future. These concepts are based on a customised procedure for gauging the need for quantitative adjustments at the sub-urban level and on the application of a set of criteria to be used in selecting suitable locations for adjustment. The article begins by presenting an overview of current trends which can be detected in current (structural) changes in the quantitative and qualitative demand for social infrastructure, and by considering the implications these entail.